1997
DOI: 10.1111/j.1442-200x.1997.tb03601.x
|View full text |Cite
|
Sign up to set email alerts
|

Behçet disease in children: A nationwide retrospective survey in Japan

Abstract: The purpose of the present study was to evaluate the incidence of BehFet disease among Japanese children and to compare their clinical features with adult patients. A first questionnaire was sent to the department of pediatrics of 1290 hospitals in Japan. Fifty-one cases of Behget disease among children under 16 years of age were reported. From a second survey, 31 cases satisfied the criteria of the BehGet's Syndrome Research Committee of Japan. Of 31 patients (14 boys and 17 girls), three cases were the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 6 publications
3
49
0
3
Order By: Relevance
“…These recurrent attacks occurred in 9/13 (70%) paediatric group and in 8/16, (50%) adult group (NS). In the paediatric group, the mean number of acute exacerbations before remission was 4.1±2.7 (range, [1][2][3][4][5][6][7][8], and the mean interval between exacerbations (corrected for variable duration of followup) was 1.4 ± 0.8 years (range, 4 months to 2.5 years). The mean number of attacks in the adult group was 2.3 ± 1.5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These recurrent attacks occurred in 9/13 (70%) paediatric group and in 8/16, (50%) adult group (NS). In the paediatric group, the mean number of acute exacerbations before remission was 4.1±2.7 (range, [1][2][3][4][5][6][7][8], and the mean interval between exacerbations (corrected for variable duration of followup) was 1.4 ± 0.8 years (range, 4 months to 2.5 years). The mean number of attacks in the adult group was 2.3 ± 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…The cutoff age of 16 years was based on earlier studies of paediatric uveitis. [1][2][3]8 The research described adhered to the tenets of the Declaration of Helsinki and was approved by the Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramnath MISRA (1) , Rajeev SINGH (2) , Sudhir SINHA (3) , A K. SASANY (4) , Amit SINGH This abstract will focus on identifying candidate bacterial antigents to which host T cell respond to and the cytokine profile of patients with reactive arthritis (ReA)/undifferentiated spondyloarthropathy (uSpA). We have previously shown that synovial fluid mononuclear cells (SFMC) from ReA and uSpA patients show proliferation to bacterial antigens that trigger ReA, i.e.…”
Section: Immunopathogenesis Of Reactive Arthritis and Undifferentiatementioning
confidence: 99%
“…In the RADIATE trial patients who had experienced prior TNFinhibitor therapy received tocilizumab at 8 mg/kg plus MTX and had 50%, 29% and 12% ACR 20, 50 and 70 responses (3).…”
Section: Division Of Rheumatology Department Of Internal Medicine IImentioning
confidence: 99%